Impact of Celebrity Endorsements on Consumers' Purchase Intentions and Overall Brand - Modi, Shweta (2007)
A sign of a celebrity is that his name is often worth more than his services. Daniel J Boorstin Despite, the hype, the risk, celebrity endorsement is the most prevailing technique of advertising today. The ongoing public fascination with celebrities today offers the marketers a wide range of creative ideas in order to attract and charm the audiences by stimulating their buying behaviour. In a place like India, where Bollywood stars and cricketers are idolized, advertisers see this as an opportunity to expand their markets and promote their brands. This dissertation focuses on evaluating the impact of celebrity endorsements on the purchase intention of these viewers and how this directly or indirectly has an overall impact on the brand/product. It begins with a literature review which gives us an insight of what the previous researchers have explored regarding this topic. The core concepts and areas of interest have been explained thoroughly. A research methodology has been structured so as to carry out the research in an effective manner. This is achieved by adopting the qualitative research method of in-depth interviews with the Indian consumers who have explained the way celebrity endorsements have been interpreted by them in their daily lives. This study has disclosed impressive insights into the topic which examines differences between endorsements with celebrities and corresponding endorsements with non-celebrities. The extent to which the media recognises the risks encountered by celebrity advertising has been discussed. It is quite fascinating to see how viewers relate themselves to these popular celebrities and how this new technique creates desire for the product in the minds of the consumers.